Client-Identified Impacts of Helpful and Hindering Events in Psychotherapy: A Qualitative Meta-analysis. (18th August 2022) - Ladmanová, Michaela; Řiháček, Tomáš; Timulak, Ladislav
Abstract: Objective: Understanding the client perspective is important for the provision of psychotherapy. The significant events paradigm, within which clients report on the most significant events of a therapy session immediately after the session, represents a useful means to explore clients' in-session experience. Method: The aim of this study was to investigate what types of client-identified impacts are reported in qualitative studies on helpful and hindering events in psychotherapy. Seventeen primary studies focusing on client-identified helpful and hindering events were identified through database searches and subsequent manual searches. The data were subjected to qualitative meta-analysis. Results: The descriptions of event impacts were classified into 12 helpful (e.g., gaining a new perspective on the self; feeling heard, understood, and accepted; and feeling engaged in the therapeutic process) and eight hindering (e.g., lacking guidance from the therapist and feeling emotionally overwhelmed) impact meta-categories. Conclusion: The findings provide an update to a previous meta-analysis by identifying several new categories of helpful event impacts and by categorizing hindering event impacts.